Improving Students™ Achievement in Writing Recount Text by Using Transitions “ Actions “ Details (TAD) Strategy - Manurung, Christian; Ownie, Sri Juriati (Universitas Negeri Medan, 2013)
ABSTRACT This research concerned on Improving Students™ Achievement in Writing Recount Text by Using Transitions “ Actions “ Details (TAD) Strategy. In this research, the writer conducted classroom action research. The subject of this research were the second year students of SMP Swasta Immanuel, Medan, class VIII-A which consisted of 36 students. This research was conducted in two cycles. Each cycle was organized in four steps, namely Planning, Action, Observation, and Reflection. Cycle II was the improvement of Cycle I. There are two kinds of data collected during the research, qualitative and quantitative data. The instruments for the quantitative data was writing test while the qualitative data was gathered through Observation Sheet, Interview Sheet and Diary Notes. Findings showed that students™ score improved from Test I to Test III. Based on the data analysis, Students™ mean in Test I was 44.33, in Test II was 61.13, and Test III was 82.66. The conclusion is that the Transitions “ Actions “ Details (TAD) Strategy can improve students™ achievement in writing recount text. Keywords: TAD Strategy, Writing, Recount